2001
DOI: 10.21236/ada412422
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Hepatic Lesions From CT Images Using Texture Features and Neural Networks

Abstract: Abstract-In this paper a computer-aided diagnostic system for the classification of hepatic lesions from Computed Tomography (CT) images is presented. Regions of Interest (ROI's) taken from non-enhanced CT images of normal liver, hepatic cysts, hemangiomas, and hepatocellular carcinomas (a total of 147 samples), have been used as input to the system. The system consists of two levels: the feature extraction and the classification levels. The feature extraction level calculates the average grey scale and 48 tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
(6 reference statements)
0
7
0
1
Order By: Relevance
“…Classification of CT scan images using hepatic lesions were proposed by Glestos et al [9]. The input CT scan image of size 500 × 500 is taken as input.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Classification of CT scan images using hepatic lesions were proposed by Glestos et al [9]. The input CT scan image of size 500 × 500 is taken as input.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…The idea so generated can be utilized this orthogonal moment for CT scan images. The classification of CT images using texture features and neural network was proposed by Glestos et al [9]. The Zernike polynomials are orthogonal to each other.…”
Section: Introductionmentioning
confidence: 99%
“…Mala et al (2010) and Gunasundari et al (2012) concluded that the performance of PNN is good when it is compared with other neural networks [10]. A classifier [11] consisting of three sequentially placed neural networks for four classes of hepatic tissues was developed. Eight co-occurrence texture features are calculated for six different values of the pixel spacing.…”
Section: Past Workmentioning
confidence: 99%
“…A classifier consisting of three sequentially placed neural networks for four classes of hepatic tissues is developed [23]. 147 samples were used, 76 of which belong to healthy ones, 19 to cysts, 28 to hemangioma and 24 to HCC.…”
Section: Multi Level Neural Networkmentioning
confidence: 99%